2014
DOI: 10.1007/s11113-014-9347-4
|View full text |Cite
|
Sign up to set email alerts
|

Employment and Occupational Mobility among Recently Arrived Immigrants: The Spanish Case 1997–2007

Abstract: The objective of this paper is to analyse occupational mobility among immigrants in Spain in two distinct stages: (1) comparing the immigrants' first job in Spain with their profession in the country of origin and (2) comparing their current occupational status with the occupational status of the first job they held in Spain. We focus on immigrants who arrived in Spain during the ''immigration boom'' that took place between 1997 and 2007, using data from the 2007 National Survey on Immigration. For our analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
(48 reference statements)
0
24
0
2
Order By: Relevance
“…Once the latter is controlled for, higher education is associated with lower risks of occupational downgrade (Simón, Sanromá, and Ramos 2014). Finally, immigrants from non-Western countries tend to experience much higher occupational downgrade and lower upward mobility compared to their Western counterparts (Stanek and Veira-Ramos 2013; Simón, Sanromá, and Ramos 2014; Fernández-Macías et al 2015).…”
Section: Immigrants’ Occupational Careers From Origin To Destination Countries: Which Role For Labor Market Contexts?mentioning
confidence: 99%
“…Once the latter is controlled for, higher education is associated with lower risks of occupational downgrade (Simón, Sanromá, and Ramos 2014). Finally, immigrants from non-Western countries tend to experience much higher occupational downgrade and lower upward mobility compared to their Western counterparts (Stanek and Veira-Ramos 2013; Simón, Sanromá, and Ramos 2014; Fernández-Macías et al 2015).…”
Section: Immigrants’ Occupational Careers From Origin To Destination Countries: Which Role For Labor Market Contexts?mentioning
confidence: 99%
“…These findings are confirmed by recent studies conducted on Southern European countries. Fernández-Macías et al. (2015) and Simón et al.…”
Section: Geographical and Occupational Mobility: Theoretical Framewormentioning
confidence: 99%
“…These findings are confirmed by recent studies conducted on Southern European countries. Ferna´ndez-Mac ıas et al (2015) and Sim on et al (2014) highlight the inconsistency of the U-shaped model in Spain, a country characterized by a wide secondary labour market: after the initial downgrade, immigrants experience limited occupational mobility. Similar results are achieved by the first comparative study on this issue (Fellini and Guetto, 2019), that considers Italy, Spain and France, three countries with a dualistic labour market.…”
Section: Geographical and Occupational Mobility: Theoretical Framewormentioning
confidence: 99%
“…In general, migrants, especially low-skilled migrants, have a more precarious and marginal position in the labor market (Tilly, 2011). Several studies have explored the occupational mobility of Latin American female migrants in Spain and concluded that a “U”-shaped pattern was observed in their occupational trajectories, mainly from domestic services to other occupations within the secondary segment of the labor market (Aysa-Lastra & Cachón, 2013; Fernández-Macías, Grande, del Rey Poveda, & Antón, 2015; Parella, Petroff, & Solé, 2013; Vidal-Coso & Miret, 2014).…”
Section: Latin American Migration During the Economic Expansion And Rmentioning
confidence: 99%